Strategies and Techniques Employed by Saba Banana Growers in Addressing the Problem of Unsold Bananas in the City of Puerto Princesa - Cabanalan, Albert (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the production conditions, drivers of unsold produce, and coping strategies of saba banana growers in selected barangays of Puerto Princesa City, Philippines. Anchored in the Sustainable Livelihood Framework (SLF), the research aimed to profile growers, identify the primary causes of unsold bananas, assess strategies and techniques employed to mitigate losses, and propose a context-specific program intervention to enhance profitability and sustainability. A descriptive-developmental research design was employed, utilizing a researcher-made survey questionnaire and Key Informant Interviews (KIIs). The study involved 91 saba banana growers selected through convenience sampling and agricultural officers as key informants. Quantitative data were analyzed using frequency, percentage, weighted mean, and ranking, while qualitative responses were examined through thematic analysis following Braun and Clarke (2006). Findings revealed that saba banana production is predominantly small-scale and labor-intensive, with low yield per hectare and substantial proportions of unsold produce and post-harvest losses. Key drivers of unsold bananas included low farmgate prices, poor fruit quality due to pests and diseases, price instability, oversupply, weak market linkages, limited storage and processing capacity, and transportation and infrastructure constraints. Although growers adopted adaptive strategies such as direct selling, mixed cropping, staggered planting, and basic sorting and grading, limited capital, technical training, cooperative participation, financial access, and institutional coordination constrained sustainable improvement. The study concludes that interconnected production, market, post-harvest, and institutional weaknesses collectively undermine profitability and industry resilience, and recommends strengthened extension services, improved post-harvest management, value-adding initiatives, cooperative development, and enhanced infrastructure support. The study supports SDG 2 (Zero Hunger), SDG 8 (Decent Work and Economic Growth), SDG 9 (Industry, Innovation and Infrastructure), and SDG 12 (Responsible Consumption and Production) by addressing agricultural productivity, livelihood stability, value-chain improvement, and food loss reduction. Its sustainability impact lies in advancing socio-economic resilience, environmental responsibility through reduced food loss and waste, and strengthened local institutional and policy support for small-scale agricultural systems.